2012
DOI: 10.4049/jimmunol.1101304
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral Injection of CpG Oligonucleotides Induces the Differentiation and Reduces the Immunosuppressive Activity of Myeloid-Derived Suppressor Cells

Abstract: Immunostimulatory CpG oligonucleotides (ODN) activate cells that express TLR 9 and have been shown to improve the host’s response to tumor antigens. Unfortunately, the immunosuppressive microenvironment that surrounds many cancers inhibits Ag-specific cellular responses and thus interferes with CpG-mediated immunotherapy. Myeloid-derived suppressor cells (MDSC) represent an important constituent of this immunosuppressive milieu. Large numbers of MDSC are present in and near tumor sites where they inhibit the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
210
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(228 citation statements)
references
References 39 publications
10
210
0
Order By: Relevance
“…While we previously showed that tumorinfiltrating monocytic MDSCs are NP þ , delivering our model cancer vaccine to the tdLN decreased the number of tumorresident Gr1 int MDSCs, which are described as monocytic and the most immunosuppressive subset, and led to MDSC maturation, thus making them less suppressive (21,36,48). CpG has been shown to affect the phenotype of MDSCs, especially monocytic MDSCs, in tumor-bearing mice, but at much higher CpG doses than we used here (32,49). We believe that our findings may be due to an effect of CpG on MDSCs and to a change in the cellular and cytokine environment in the tumor following immunization.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…While we previously showed that tumorinfiltrating monocytic MDSCs are NP þ , delivering our model cancer vaccine to the tdLN decreased the number of tumorresident Gr1 int MDSCs, which are described as monocytic and the most immunosuppressive subset, and led to MDSC maturation, thus making them less suppressive (21,36,48). CpG has been shown to affect the phenotype of MDSCs, especially monocytic MDSCs, in tumor-bearing mice, but at much higher CpG doses than we used here (32,49). We believe that our findings may be due to an effect of CpG on MDSCs and to a change in the cellular and cytokine environment in the tumor following immunization.…”
Section: Discussionmentioning
confidence: 89%
“…We used the TLR9-ligand CpG as adjuvant for its Th1-skewing properties (12) and ability to boost antitumor immunity (30)(31)(32). B16-F10-bearing mice were immunized intradermally in all four footpads 4, 7, 11, and 15 days after inoculation with 40 mg TRP-2 180-188 and 4 mg CpG conjugated onto nanoparticles (NP-TRP-2 þ NP-CpG) or in soluble form (TRP-2 þ CpG; Fig.…”
Section: Nanoparticle Conjugation Enhances Cell Targeting and Therapementioning
confidence: 99%
“…In addition, complement factor 4 produced by myeloid cells may regulate spontaneous GC reactions in self-reactive B cell receptor transgenic mice [14]. We therefore suggest that the chronic inflammatory milieu developing in female (NZB x NZW)F1 mice affect a population of regulatory neutrophils (Nregs) either via the induction of apoptosis (or maybe even NETosis) [4,83] or via the induction of a differentiation program driving the development of non-immunosuppressive cells such as dendritic cells, macrophages or mature neutrophils, as previously suggested [83][84][85].…”
Section: Anti-inflammatory Properties Of Neutrophils In Lupusmentioning
confidence: 92%
“…Hence, injection of tumor cells in combination with CD11b + Gr1 + cells in mice prompt tumor growth [249]. Accordingly, depletion of Gr1 + cells in tumor-bearing mice leads to delayed tumor growth, suggesting MDSC as potential targets for anti-cancer therapy [250][251][252][253][254][255][256]. A report by Youn and colleagues indicated that CD11b + Gr1 + cells from naïve tumor-free mice are not immune suppressive [243].…”
Section: Myeloid Derived Suppressor Cells (Mdsc)mentioning
confidence: 99%